Influence of Multi-Role Interactions in Community Group-Buying on Consumers’ Lock-In Purchasing Intention From a Fixed Leader Based on Role Theory and Trust Transfer Theory - Wu, Jingjing; Chen, Yiwei; Pan, Hao; Xu, Anxin (Frontiers in Psychology, 2022)
Community group-buying platforms are increasingly relying on the interaction between the group-buying leader and consumers, thereby achieving the customer lock-in. In view of this, it is crucial to understand how the group-buying leader to establish a long-term transaction relationship with consumers. In this study, we construct a model based on the role theory and trust transfer theory, and identify two types of interactions of the group-buying leader (i.e., role interaction of merchant and role interaction of friend) and two types of consumer trust (i.e., community group-buying trust and interpersonal trust). Then, the mechanism that how different role interactions of the group-buying leader can be transformed into the lock-in purchasing intention of consumers is further clarified. By interviewing 430 consumers with community group-buying experience in the community through offline questionnaire, the research model has been proven to be effective. To be specific, both role interactions of the merchant and friend can impose a positive impact on interpersonal trust, which will also lead to the trust in community group-buying, and thus enhance the lock-in purchasing intension of consumers from a fixed leader. Overall, this study has made certain contributions to the study of customer relationship. In theory, this study further explains the explanation mechanism of the “acquaintance marketing” phenomenon. Moreover, this study adopts the role theory to analyze the differences of different role interactions of the group-buying leader in relationship quality and purchase decision-making, and employs the trust transfer theory to expand the trust transfer effect from the interpersonal trust of the group-buying leader to the trust in community group-buying. In practice, this study provides a new perspective and practical reference for community group-buying enterprises and the group-buying leader on how to better manage customers and maintain a long-term and stable customer relationship.